Kyrgyz Republic - The Garment Sector : Impact of Joining the Customs Union and Options to Increase Competitiveness - World Bank (Washington, DC, 2015)
This note analyzes the impact that joining the Eurasian Customs Union will have on the Kyrgyz Republic s garment sector and options for improving the sector s competitiveness. The paper finds that joining the Eurasian Customs Union will lead to higher prices for the textiles and cloth used in garment production. This will increase the cost of producing garments in the Kyrgyz Republic and will more than likely place downward pressure on exports from the Kyrgyz Republic, which will induce firms, particularly less competitive ones, to exit from the garment sector. To offset the increase in cost from higher tariffs, it is recommended that the Kyrgyz Government aims to increase productivity by lifting the constraints that reduce the sector s competitiveness. This can be done through interventions to increase the use of new technology, improve knowledge of consumer markets, and strengthen skills and education. This paper discusses these issues in four parts. The first provides an economic context for the discussion (Section I), which is followed by a discussion of the development of the garment sector and its importance for the economy (Section II). The paper then assesses the impact that joining the Customs Union (Section III) will have on production costs in the garment sector. Section IV describes the constraints the sector s competitiveness and possible interventions to lift these constraints.